Effect of Phenolics from Aeonium arboreum on Alpha Glucosidase, Pancreatic Lipase, and Oxidative Stress; a Bio-Guided Approach - Marwah M. Alfeqy; Seham S. El-Hawary; Ali M. El-Halawany; Mohamed A. Rabeh; Saad A. Alshehri; Aya M. Serry; Heba A. Fahmy; Marwa. I. Ezzat (Pharmaceutics, 2023)
Metabolic syndrome (MetS) is a global issue affecting over a billion people, raising the risk of diabetes, cardiovascular disorders, and other ailments. It is often characterized by hypertension, dyslipidemia and/or obesity, and hyperglycemia. Chemical investigation of Aeonium arboreum (L.) Webb & Berthel led to the isolation of six compounds, viz. β-sitosterol, β-sitosterol glucoside, myricetin galactoside, quercetin rhamnoside, kaempferol rhamnoside, and myricetin glucoside. Interestingly, A. arboreum’s dichloromethane (DCM), 100 and 50% MeOH Diaion fractions and the isolated compound (quercetin-3-rhamnoside) revealed potent α-glucosidase inhibitory activity, especially 50% Diaion fraction. In addition, they also showed very potent antioxidant potential, especially the polar fractions, using DPPH, ABTS, FRAP, ORAC, and metal chelation assays. Notably, the 50% Diaion fraction had the highest antioxidant potential using DPPH and ORAC assays, while the 100% Diaion fraction and quercetin-3-rhamnoside showed the highest activity using ABTS, FRAP, and metal chelation assays. Also, quercetin-3-rhamnoside showed a good docking score of −5.82 kcal/mol in comparison to acarbose. In addition, molecular dynamic stimulation studies illustrated high stability of compound binding to pocket of protein. Such potent activities present A. arboreum as a complementary safe approach for the management of diabetes mellitus as well as MetS.